Development Of Integreted Science E-LKPD Based On Scientific Approach On The Energy Theme For Science Learning In Junior High Schools - Niffa Aji Fatahillah; Khairil Arif (Department of Science Education, 2022)
In the 2013 curriculum, the learning process is emphasized on the application of a scientific approach, and teachers are also required to be able to provide innovation in teaching materials. The results of observations in several junior high schools in Tanjung Mutiara sub-district, the teaching materials used are still limited to textbooks, in the learning process teachers still use the lecture or discussion method, and the application of the scientific approach has not been applied as a whole. Based on these problems, a research has been carried out that aims to determine the level of validity and practicality of the Integrated Science-Based E-LKPD Scientific Approach on the Energy Theme for Science Learning in SMP/MTs. This type of research is Research and Development (R&D) using a 4-D model consisting of four stages, namely: define, design, develop, and disseminate. Given the limited time this research is limited to the develop stage. The data collection instrument used was a validity and practicality questionnaire. The subjects of this study were three lecturers in the science education department as expert validators, two science teachers as practicalists and thirty seventh grade students at SMP Negeri 1 Tanjung Mutiara as practicalists. The data of this study are primary data obtained from the results of validity and practicality questionnaires. Data were analyzed using Cohen's kappa formula. The results of the validity of the E-LKPD obtained a value of 0.89 with a very high validity category. The practicality test value of the E-LKPD obtained from the teacher's response is 0.95 with a very high practicality category, while the practicality test value of the E-LKPD obtained from the student's response is 0.92 with a very high practicality category. So it can be concluded that the Integrated IPA E-LKPD Based on a Scientific Approach on the Energy Theme is valid and practical to use.